Does Private and Cost-Priced Higher Education Produce Poor Quality? - Peter Galasi; Julia Varga (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2002)
Since the beginning of the transition, Hungarian higher education has been undergoing continuous transformation. The number of students in higher education more than doubled, and this was accompanied by the appearance of newly founded church-run and private higher education institutions and newly established cost-priced places. The paper focuses on the potential negative effects private and cost-priced higher education might have on the quality of the education and students by making use of labour market success indicators (wages and labour market status) with the help of multivariate estimation techniques. A unique data set, the Second Fidv Survey, is used which provides information about the September 2000 labour market situation of persons graduated from higher education in 1999. The results suggest that education at cost-priced, state funded places and private higher education institutions provides essentially the same level of knowledge or produces the same educational quality as measured by wages. No negative effect has been detected as for the labour market status of exstudents. Students from cost-priced places and private institutions experience the same unemployment probability, whereas the overall employment probability of students graduated from cost-priced places is higher than that of persons studied at state-funded places. One can conclude that although the opportunity of establishing more and more cost-priced places might have been advantageous for higher education institutions so as to increase their revenues, they have shown some selfrestraint in this respect, and there is no sign that the increase in costpriced places has led to lower quality workers.
Keywords: 330